Evidence of hypericin photoinactivation of E. faecalis: From planktonic culture to mammalian cells selectivity up to biofilm disruption - Souza Amaral, Larissa; Orzari Ribeiro, Anderson; Rodrigues Perussi, Janice (Photodiagnosis and photodynamic therapy, 2020)
[Display omitted] •HY-aPDT make possible a complete eradication of Enterococcus faecalis in planktonic form.•The membrane disruption and bacterial killing have been proven by scanning electron microscopy, transmission microscopy and fluorescence microscopy.•HY-aPDT is selective for photoinactivation of planktonic E. faecalis since it is not toxic to fibroblasts under the used conditions.•Sequential in vitro experimentation involving planktonic assay, selectivity on fibroblasts and biofilm assays help to understand the sensitivity profile of HY for E. faecalis. Antimicrobial Photodynamic Therapy (aPDT) is an alternative for microbiological inactivation. The aPDT is a method that uses a photosensitizer (PS) excited by visible light at the appropriate wavelength and the molecular oxygen present in the tissues resulting in the production of reactive oxygen species, which causes oxidative damage to biological molecules. This study aimed to perform an in vitro experimental sequence for photoinactivation of E. faecalis using Hypericin (HY) from planktonic culture to selectivity assays using mammalian cells up to biofilm. The results show that E. faecalis rapidly absorb HY. The levels of inactivation of E. faecalis reached up to 99% in planktonic culture. Transmission and Scanning Electron Microscopy demonstrate the remarkable morphological alterations resulting from photooxidation being the loss of membrane integrity assessed by fluorescence microscopy combined with a LIVE/DEAD™ kit. HY did not present cytotoxicity to the fibroblasts cell at the used conditions proving to be a selective molecule. Finally, 60% of photoinactivation was observed in the biofilm of E. faecalis when subject to HY-aPDT. These outcomes show the advantages of sequential in vitro experiments besides showing that HY is a potential PS for clinical trials due to its selectivity and photodynamic effect. This study also draws attention to the benefits of using methodologies that can evidence the antimicrobial effect beyond the typical constellation of cell death.